2011
DOI: 10.1186/1750-9378-6-s2-s10
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer health and cultural beliefs of black men: The Florida Prostate Cancer Disparity Project

Abstract: BackgroundSince behavioral factors are significant determinants of population health, addressing prostate cancer (CaP)-related health beliefs and cultural beliefs are key weapons to fight this deadly disease. This study investigated the health beliefs and cultural beliefs of black men relative to CaP, and the key socio-demographic correlates of these beliefs.MethodsThe study design was a cross-sectional survey of 2,864 Florida black men, age 40 to 70, on their perceived susceptibility, perceived severity, atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…This is consistent with the findings of a US study, which reported moderate perceived susceptibility and perceived severity of prostate cancer in black males. 24 Worryingly, 37% of those who declined indicated that they would rather not know they have cancer; this, again, echoes their fears of the disease and perceived negative consequences of it being diagnosed.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with the findings of a US study, which reported moderate perceived susceptibility and perceived severity of prostate cancer in black males. 24 Worryingly, 37% of those who declined indicated that they would rather not know they have cancer; this, again, echoes their fears of the disease and perceived negative consequences of it being diagnosed.…”
mentioning
confidence: 98%
“…23,24 The questionnaire in this study did not collect specific information to assess this, although the main reasons cited by participants for choosing or declining investigation provide useful insights in this regard. In total, 86% of those declining prostate cancer investigation were black males, around half of whom cited low risks as the main reason for their choice.…”
mentioning
confidence: 98%
“…The originality and relevance of this network will rely on the wide genetic diversity of its populations. Indeed, most African-Caribbean's have ancestries from Benin, Nigeria, Ghana and Senegal because of the transatlantic slave trade and may share common polymorphism [19].…”
Section: Set Up and Management Of A Biobank Network In The Caribbeanmentioning
confidence: 99%
“…In addition to the above factors, Odedina et al [6] have noted some health behavioural factors like, perceived susceptibility of getting prostate cancer, perceived severity of the disease and sequelae, D DAVID PUBLISHING perceived benefits about reducing the risk of disease; perceived barriers impacting early disease detection and prevention behaviours, cues to action in activating preventive and early detection measures and perceived behavioural control as among other factors impacting on the burden of this disease among Black men.…”
mentioning
confidence: 99%